Electrochemical Determination of Synephrine by Hydrophilic Interaction Liquid Chromatography Using a Zwitterionic Monolith Column. Issue 9 (2nd May 2016) - Sakai, Yuki; Kotani, Akira; Umemura, Tomonari; Mori, Yukiko; Kusu, Fumiyo; Yamamoto, Kazuhiro; Hakamata, Hideki
Abstract: A sensitive method for the electrochemical determination of synephrine (SYN) by hydrophilic interaction liquid chromatography (HILIC) has been developed. Optimal chromatographic separation and high sensitive determination by HILIC with electrochemical detection (HILIC‐ECD) was achieved using a sulfobetaine‐type zwitterionic monolith column (100×1.02 mm, i.d.), a mixture of 10 mM sodium phosphate (pH 4) and acetonitrile (20 : 80, v/v) as mobile phase, and a glassy carbon working electrode which was applied with a potential at +1.0 V vs. Ag/AgCl. The chromatographic peak height of SYN was proportional to the concentration from 5.0 µg/L to 1.0 mg/L ( r =0.999). The detection limit of SYN ( S/N =3) was 3.7 pg on the column. Moreover, the present HILIC‐ECD could be applied to the accurate and precise determination of SYN in Aurantii nobilis Pericarpium . In conclusion, we have demonstrated that an ECD is one of useful detection methods applicable to HILIC. Abstract :